2017
DOI: 10.1111/tpj.13766
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of lysine acetylation provides strong evidence for involvement of acetylated proteins in plant meiosis and tapetum function

Abstract: SUMMARYProtein lysine acetylation (KAC) is a dynamic and reversible post-translational modification that has important biological roles in many organisms. Although KAC has been shown to affect reproductive development and meiosis in yeast and animals, similar studies are largely lacking in flowering plants, especially proteome-scale investigations for particular reproductive stages. Here, we report results from a proteomic investigation to detect the KAC status of the developing rice anthers near the time of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 61 publications
(98 reference statements)
1
25
0
Order By: Relevance
“…In rice germinating embryo, 699 PKA sites on 389 proteins were found to be acetylated, including 144 sites that were simultaneously modified by succinylation [ 26 ]. In an effort to discover the PKA in rice anthers in the stage of meiosis, Li et al (2018) identified a total of 1354 PKA sites in 676 proteins, which are mostly related to chromatin silencing, protein folding, and fatty acid biosynthetic processes [ 27 ]. There were also 44 and 692 lysine acetylated proteins that were identified from suspension cells and grain-filling stage seeds [ 24 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rice germinating embryo, 699 PKA sites on 389 proteins were found to be acetylated, including 144 sites that were simultaneously modified by succinylation [ 26 ]. In an effort to discover the PKA in rice anthers in the stage of meiosis, Li et al (2018) identified a total of 1354 PKA sites in 676 proteins, which are mostly related to chromatin silencing, protein folding, and fatty acid biosynthetic processes [ 27 ]. There were also 44 and 692 lysine acetylated proteins that were identified from suspension cells and grain-filling stage seeds [ 24 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This also intrigued researchers to explore PKAs in rice. So far, at least 8 independent cases have been reported regarding the profiling of PKA sites, peptides, and proteins in rice seedlings, reproductive organs, and leaves under oxidative stress, which yielded the identification of over 8599 PKA sites and 4990 proteins [ 7 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Despite efforts being made on rice, the previous studies only explored the tip of the iceberg of rice acetylome, given that rice genome contains over 56,000 protein coding genes [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meiotic proteome complexity was reduced based on: comparative proteomics combined with transcriptomics in A. thaliana ( Lu et al, 2016 ); ASY1 affinity proteomics in B. oleracea ( Osman et al, 2018 ); proteomic approaches focusing on the identification of posttranslational protein modifications (PTMs) in rice ( Ye et al, 2015 ; Li et al, 2018 ). Surprisingly, a comparison of available Arabidopsis flower bud proteomes suggests that protein detection was not saturated ( Lu et al, 2016 ).…”
Section: Proteomic Approachesmentioning
confidence: 99%
“…Proteomics from rice anthers identified 357 acetylated proteins including eight rice homologs of known meiotic genes ( Li et al, 2018 ). A positive correlation of simultaneous acetylation and phosphorylation of candidates functionally enriched for ribosome assembly, protein translation, UPS, and RNA degradation was found, further linking these processes to plant meiosis (see section “Meiotic Transcriptome”).…”
Section: Proteomic Approachesmentioning
confidence: 99%
See 1 more Smart Citation